2010
DOI: 10.7863/jum.2010.29.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sonographic Automatic Volume Calculation in Measuring Fetal Cardiac Ventricular Volumes Using 4-Dimensional Sonography

Abstract: There was good agreement between cardiac volumes measured with VOCAL and sonoAVC. Sonographic automatic volume calculation represents a rapid technique for estimating fetal stroke volume and promises to become the method of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
(32 reference statements)
2
29
0
Order By: Relevance
“…Like RT3DE, STIC volumes can also be calculated automatically. Rizzo G et al reported good agreement between VOCAL and sonographic automatic volume calculation (sonoAVC) for fetal ventricular volume measurements (intraclass correlation coefficients 0.978 and 0.985 for LV and RV), and the time necessary to measure the SV was significantly shorter with sonoAVC (2.8 versus 11.7 minutes) than with VOCAL [28].…”
Section: Discussionmentioning
confidence: 97%
“…Like RT3DE, STIC volumes can also be calculated automatically. Rizzo G et al reported good agreement between VOCAL and sonographic automatic volume calculation (sonoAVC) for fetal ventricular volume measurements (intraclass correlation coefficients 0.978 and 0.985 for LV and RV), and the time necessary to measure the SV was significantly shorter with sonoAVC (2.8 versus 11.7 minutes) than with VOCAL [28].…”
Section: Discussionmentioning
confidence: 97%
“…While rotating at a 6° angle around the fixed axis (plane A), 30 slices were obtained to manually trace the splenic contours along a particular section. The splenic volume and 3D rendering were generated automatically (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…A solid body of evidence suggests that 4D sonography with STIC facilitates examination of the fetal heart 3 , 4 , 5 , 11 37 and may also be used to evaluate fetal cardiac function 18 , 22 , 27 , 30 , 31 , 33 , 38 46 . This modality has also been used in the prenatal evaluation and diagnosis of congenital heart disease (CHD) 2 , 20 , 47 71 because it improves the ability to identify complex intracardiac relationships and can shorten the examination time 3 , 17 , 72 .…”
Section: How To Perform 4d Sonography With Sticmentioning
confidence: 99%